The reptiles - Carr, Archie Fairly, 1909-; Time-Life Books (Alexandria, Va. : Time-Life Books, 1967)
Traces the evolution of reptiles and discusses the physical characteristics and habits of the three main groups existing today--turtles, lizards and snakes, and the crocodilians.
Includes index.
Bibliography: p. 187.
Keywords: Reptiles; Reptiles